Collection and conservation of endangered medicinal plant species diversity for maintaining ecological balance - Tirkey, Alice; Nagvanshi, Disha; Sahu, Mukesh (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> India is one of the 12 mega biodiversity centre. Chhattisgarh state located centrally in India has approx. 44% forest area are the principle repository of large number of medicinal and aromatic plants due to this C.G. is declared as herbal state in 2001. The flora of medicinal and aromatic plant is depleting quit fast due to use of forest land in other purpose and over exploitation of herbs. The state is dominated by tribal population and major tribal population depend on forest for fiber, food, fuel, fodder, medicine. Due to over exploitation of herbs and use of forest land in other purpose large number of plant species become rare and endangered. Thus collection of different made for the collection of multi crop collecting mission along with particular medicinal and aromatic plant from Achanakmarg, Lamni, Ataria, Keochi, Dhamtari, Keregaon, singhpur medicinal and aromatic plant, its conservation and characterization for its various agro-morphological and quality traits will help in producing the quality product and for improvement in particular species genetically. With this objective exploitation was made Dugli, Nagri and near by places which are the hot spot of flora diversity and trading area of medicinal plants of C.G. The present investigation revealed that the forest are of Dhamtari Keregaon, South Singpur, Dugli and Nagri and near by places and Bilaspur District (Achanakmarg ,Lormni, Ataria, Keonchi and near by place) was dominated by herbs 47%, trees 24%, climbers 14% and 15% shrubs were as 52% herbs, 16% shrubs, tree 19% trees and 12% climber, climbing shrus 1% respectively. The break up of medicinal plants by their plant parts utilized in general for the treatment of different diseases contains approximately 32% roots, 18% leaves, 12% bark, 9% stem, 9% seed, 8% fruit, 8% whole plant, 2% flower, 1% gum/ latex and 1% wood approximately. The different medicinal plants are utilized for fever, joint pain, diarrhaea, skin ailment, cough and cold, jaundice, bronchitis, liver problem etc. Many of the medicinal plant species are in list of endangered taxa of the state such as safed musli (Chlorophytum borivilianum), kali haldi (Curcuma coesia), van haldi (Curcuma aromatic), tikhur (Curcuma angestifolia), kalihari (Gloriosa superb), sarpgandha (Rouwalfia sarpentina), kalmegh (Andrographis paniculata) etc. are few of them were collected, multiplied and characterize in herbal garden of IGKV, Raipur. Hence conservation and its strategies cultivation of these plant species will help in maintaining ecological balance so that this heritage can be used and exploited wisely through judicious management for future generation. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->